Dukungan Keluarga dalam Menghadapi Kejadian Depresi Postpartum Pada Ibu Nifas - Namirotus Sa’diyyah; Rita Yulifah; Jamhariyah Jamhariyah (Journal of Innovative and Creativity, 2025)
The postpartum period is a transitional period that can cause a crisis in the life of the mother and family, because at this time the mother will experience physical and psychological changes. The purpose of this study was to describe the description of family support and the forms of support that can be provided to deal with the incidence of postpartum depression. The method used is descriptive quantitative and qualitative with a literature review research design, researchers identify 15 journals with 10 national journals and 5 international journals. 9 journals describing husband's support, 5 social support journals and 1 family support journal. After the study was conducted, the results obtained From 15 scientific articles found forms of support that can be given to deal with the incidence of postpartum depression in postpartum mothers 5 journals about emotional support, instrumentasl, information and appreciation. 1 journal on infant care support. 2 journals about support provided by health workers. 6 journals of social support provided by the family and 1 journal that discusses informational support, rewards and group support. Therefore, it can be concluded that the support provided by the family/husband in the form of emotional support, appreciation, instrumental and information or social support can help mothers face the postpartum period and reduce the risk and level of depression experienced by postpartum mothers.